Auswirkungen und alternative Ausgestaltung der Modulation von Direktzahlungen; Impacts and Alternative Options of Modulation of Direct Payments - Werner Kleinhanss (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– The system of direct payments in the European Union's Common Agricultural Policy (CAP) is being criticised with respect to the level, unequal distribution and allocation effects on production. Besides the decoupling of direct payments a modulation and a partial transmission to the second pillar of CAP are proposed. Modulation on a voluntary basis was already introduced in Agenda 2000. In its Mid-term Review of the Agenda the Commission proposes an obligatory dynamic modulation scheme including the capping of direct payments beyond a threshold of 300 000 Euro. Possible impacts of the Commission's proposal are assessed with simulations based on farm accounting data of EU-FADN. Distribution effects between farm sizes and member states are unveiled. Alternate options with regard to capping and progressive reductions of direct payments are analysed. Due to the different distribution of direct payments, farms of EU Member states will be affected differently by the proposal of the Commission: The franchise of 5 000 Euro will exempt from modulation about tw -thirds of farms being represented by FADN respectively 15 % of the premium volume. About 80 % of the volume are subject to proportional reductions and 5 % fall off due to capping. More than four fifths of the capping affects Eastern Germany alone.The capping measurement leads to large distributional effects between farm sizes and between member states: In the first step of the dynamic modulation, premia beyond the franchise are reduced by 3 % while they are totally taken away beyond the capping threshold. Direct payments to large farms in Eastern Germany would be reduced by more than half. Due to drastic income shortfalls farm adaptations by splitting-up the farm enterprises or reducing the number of hired workers would be induced. An alternate scheme of modulation based on a progressive reduction of direct payments has been proposed. Elements of this system are a franchise, dynamic progressive reductions of direct payments within a progressive zone and proportional premia reductions beyond the upper limit of the progressive zone. There is no capping and with regard to administration purposes no other factors than the level of direct payments are included. With the determination of a few parameters - the franchise, the progression zone and the minimum and maximum rates of reduction - the system can be handled flexibly in view of social and budgetary objectives. Compared to the Commission's proposal farms entitled to less than 100 000 Euro of direct payments would forfeit less money under the progressive reductions system. Farms entitled to 100 000 to 300 000 Euro of direct payments would lose moderately more. Among the large farms however, premia reductions would be distributed more evenly and never exceed the maximum rate of e.g. 35 % while by the capping as proposed by the Commission affected farms could lose much more with the average loss increasing from 35 to 42 % of original entitlements.
Keywords: 330; Agrarsubvention; EU-Agrarpolitik; Wirkungsanalyse; EU-Staaten